Clinical and Radiological Features of Cronkhite–Canada Syndrome: A Case Report - Lokesh, Lokesh; Jindal, Vikas; Das, Prasenjit; Yadav, Rajni; Makharia, Govind K.; Madhusudhan, Kumble Seetharama (Journal of Gastrointestinal and Abdominal Radiology, 2022)
Cronkhite–Canada syndrome is a rare non-hereditary disease characterized by gastrointestinal hamartomatous polyposis and protein-losing enteropathy. The presenting symptoms are onychodystrophy, skin pigmentation, alopecia, weight loss, and diarrhea. Diagnosis is suggested by a combination of clinical, imaging, and endoscopy findings, and histology is necessary for confirmation. Here we describe a case of a 54-year-old man presenting with watery diarrhea, colicky abdominal pain, nasal obstruction, and weight loss for 6 months. Endoscopy showed multiple polyps in the stomach, duodenum, and colon. These were seen on computed tomography (CT) enterography along with polyps in the small bowel. A final diagnosis was made after the biopsy.
Keywords: Cronkhite–Canada syndrome; intestinal polyps; hyperpigmentation; malabsorption; protein-losing enteropathy